The Bloomsbury Handbook of the Internationalization of Higher Education in the Global South - Carolina Guzmán-Valenzuela (University of Johannesburg, 2021)
In this review of The Bloomsbury Handbook of the Internationalization of Higher Education in the Global South, Carolina Guzmán-Valenzuela discusses why this book might come to be considered a first port-of-call for recognising that internationalisation of higher education is a narrative firmly rooted in western ideologies and which serves as a totalising imaginary. The book, Guzmán-Valenzuela argues, helps to understand the many faces and dimensions of internationalisation in higher education and invites us to think further about what is appropriate to each country given its historical, cultural, political, educational and epistemic background. For Guzmán-Valenzuela, this is a crucial task.